PENGARUH LATIHAN FISIK TERHADAP PERUBAHAN KEKUATAN OTOT PEMAIN FUTSAL CHERUBIM FC - Tang, Aco; Hendrik, Hendrik; Nining Wean, Inosensius Gabriel (UNIVERSITAS NEGERI MAKASSAR, 2020)
This study was quasy experimental involving treatment variables, namely physical exercise, while the response variable is muscle strength. The study design was a pretest-post test two group design. The target population is the futsal player Cherubim Fc as many as 25 people, while the sample of this study is the futsal player Cherubim Fc as many as 20 people, at the time of the study, with random sampling technique divided into 2 (two) groups, one treatment group totaling 10 people and one control group of 10 people. This study uses leg dynamometer to measure muscle strength before and after intervention twice a week for 6 weeks. The provision of physical exercise resulted in an increase in muscle strength of 36.25 Â± 11.307 while in the control group an increase of 7.92 Â± 9643. In the different influence test, it was foundthat the value of p = 0,000 <0.05 which means that there were significant differences between the treatment and control groups. It is recommended to coaches to provide physical training to increase the muscle strength of futsal players Cherubim Fc.